2012
DOI: 10.1155/2012/545483
|View full text |Cite
|
Sign up to set email alerts
|

Should Any Workplace Be Exempt from Smoke-Free Law: The Irish Experience

Abstract: Background. In 2004, the Irish Government introduced national legislation banning smoking in workplaces; with exemptions for “a place of residence”. This paper summarises three Irish studies of exempted premises; prisons, psychiatric hospitals and nursing homes. Methods. PM2.5 and nicotine were measured in nursing homes and psychiatric hospitals, in addition to ultrafine particles in the hospitals. In the prisons, officers (n = 30) completed exhaled breath Carbon Monoxide (CO) measurements. Questionnaires dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 7 publications
2
4
0
Order By: Relevance
“…Consistent with almost every other study within both general 9-11 , and specific populations or settings 3,12,13 , including prisons and forensic psychiatric units 16-20 , non-smokers were more likely to be positive about prison smoking bans. They were also less likely to suggest their introduction would bring difficulties.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Consistent with almost every other study within both general 9-11 , and specific populations or settings 3,12,13 , including prisons and forensic psychiatric units 16-20 , non-smokers were more likely to be positive about prison smoking bans. They were also less likely to suggest their introduction would bring difficulties.…”
Section: Discussionsupporting
confidence: 74%
“…Very few surveys have been conducted on opinions about smoking restrictions in prisons; also potentially relevant are surveys in secure hospitals. An Irish study surveyed 90 prison staff among those from other workplaces, reporting agreement with: ‘Should there be a smoking ban in prisons?’ (41% yes); prohibition of smoking in enclosed areas (79% agreed); and whether a complete ban would ‘create more problems in the prison’ (88% yes) 16 . As with population or other workplace-based studies, this study found greater support for restrictions among non-smokers.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, according to their ECO level, the non-exposed subjects in our sample would be classified as non-smokers, the exposed to cigarette smoke as smokers, and those exposed to waterpipe smokers as heavy smokers, although all declared to be non active smokers. Actually, the fact that non active smoking workers, exposed to SHS, have ECO levels that would classify them as active smokers was also seen in other studies [27,28]. In the multivariate analysis, exhaled levels of CO were also positively affected by the weekly hours of occupational exposure to waterpipe smoke by the hospitality workers, and by daily hours of exposure to cigarette smoke in universities as well, but to a lesser extent.…”
Section: Ijomeh 2014;27(4)supporting
confidence: 62%
“…McCaffrey et al reported that air quality measures in Irish psychiatric hospitals were broadly similar to those found in Irish bars prior to the 2004 Irish smoke-free legislative ban. 16 Their study identified excessively high particulate concentrations detected in psychiatric hospitals and nursing homes – settings in which the introduction of smoking bans was initially exempt.…”
Section: Mental Healthmentioning
confidence: 99%